2017
DOI: 10.1111/add.14085
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a web‐based intervention with and without guidance for employees with risky drinking: results of a three‐arm randomized controlled trial

Abstract: AimsTo test the efficacy of a web‐based alcohol intervention with and without guidance.DesignThree parallel groups with primary end‐point after 6 weeks.SettingOpen recruitment in the German working population.ParticipantsAdults (178 males/256 females, mean age 47 years) consuming at least 21/14 weekly standard units of alcohol (SUA) and scoring ≥ 8/6 on the Alcohol Use Disorders Identification Test.InterventionFive web‐based modules including personalized normative feedback, motivational interviewing, goal set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(122 citation statements)
references
References 52 publications
7
112
1
2
Order By: Relevance
“…The five studies on alcohol intake reported conflicting results. Two studies on alcohol intake reported small treatment effects (48,76), while two other studies did not use comparable measures and reported improvements only for binge drinking and consumption reduction (34,35). The fifth study (68) reported the opposite effect, namely, higher alcohol consumption in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…The five studies on alcohol intake reported conflicting results. Two studies on alcohol intake reported small treatment effects (48,76), while two other studies did not use comparable measures and reported improvements only for binge drinking and consumption reduction (34,35). The fifth study (68) reported the opposite effect, namely, higher alcohol consumption in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study among college students identified that they preferred informal sources of support, such as talking to friends, over online tools (Buscemi et al, 2010). Other research suggests that anonymity offered by online tools may be more appealing for those with harmful alcohol use, who may be concerned about stigma associated with help seeking (Khadjesari, Stevenson, Godfrey, & Murray, 2015), and they may be convenient for people who work full time (Boss et al, 2018). However, digital interventions may not be accessible to some population groups such as the homeless, those in prison, or the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention satisfaction. At post-treatment (T1) and the first follow-up (T2) participants' satisfaction with the personalized tele-based coaching is measured using a German Version of the Client Satisfaction Questionnaire (CSQ-8, adapted version for internet interventions: CSQ-I) (66)(67)(68). In the IG, the CSQ-I will be adapted for telephone coaching (the original CSQ-8 is validated only in face-to-face contexts).…”
Section: Intervention-related Outcomesmentioning
confidence: 99%
“…In the IG, the CSQ-I will be adapted for telephone coaching (the original CSQ-8 is validated only in face-to-face contexts). The CSQ-8 as well the CSQ-I consist of eight items (4-point Likert scale) and report a high internal consistency (α = 0.87 and 0.93) (67,68). An adapted version of the CSQ-I will be used for the assessment of participant's satisfaction with the information material received in the CG.…”
Section: Intervention-related Outcomesmentioning
confidence: 99%